Serum Levels of Hepcidin in Patients with Biopsy-Proven Nonalcoholic Fatty Liver Disease - YILMAZ, YUSUF (MARY ANN LIEBERT INC, 2011)
Background: Research suggests the presence of mild-to-moderate iron overload in patients with nonalcoholic fatty liver disease (NAFLD). The role played by hepcidin, the master regulatory hormone of systemic iron metabolism, in the pathogenesis of NAFLD remains controversial. The aims of this study were to: (1) Evaluate serum hepcidin levels in patients with biopsy-proven NAFLD and age-and sex-matched controls and (2) identify the potential associations of hepcidin with the clinical and biochemical characteristics of the study participants. Methods: Serum levels of hepcidin were measured by enzyme-linked immunosorbent assay and compared in 88 patients with NAFLD (56 males and 32 females; mean age, 44 +/- 11 years) and 88 controls (51 males and 37 females; mean age, 43 +/- 12 years). Moreover, concentrations of hepcidin were assessed in relation to the general characteristics of the study participants and the results of liver biopsy. Results: Serum levels of hepcidin were significantly higher in patients with NAFLD (63.5 +/- 19.5 ng/mL, P < 0.001) compared with controls (32.7 +/- 8.3 ng/mL). Multivariable regression analyses in patients with NAFLD showed that hepcidin levels were positively associated with total cholesterol (beta = 6.9, t = 3.3, P < 0.01) and triglycerides (beta = 1.4, t = 2.4, P < 0.05), but not with iron parameters, histological staging, and pathological characteristics of NAFLD. Conclusions: Although subject to future confirmation, our data suggest that hepcidin levels are elevated in NAFLD and could be associated with lipid parameters in this setting.
Keywords: IRON OVERLOAD SYNDROME; METABOLIC SYNDROME; ASSOCIATION; PROHEPCIDIN